APLIKASI CAR FOLLOWING MODEL UNTUK SIMULASI ARUS LALU LINTAS DI ALUR PELAYARAN SUNGAI - Kadarsa, Edi; Lubis, Harun Al Rasyid S.; Sjafrudin, Ade; Frazila, Russ Bona (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
To develop river transport in Indonesia, traffic flow research is required to analyse fairway capacity and level of service, and also transportation safety. Due to vessel traffic is insignificant, the research should be undertake using simulation model. To construct the simulation model, the vessel’s interaction rules in the system are required. Car following model may be applied to regulate the vessels’ interaction by perform some adjustments to characteristics of river, vessels, and driver. This research aims to select car following model and determine rezime to formulate the realistic driver behavior in the system, without discuss the river velocity effect to car following model.